2020
DOI: 10.1155/2020/8883704
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Evaluation Study of the Geometric Changes of Root Canal Preparation and the Quality of Endodontic Treatment

Abstract: Introduction. The geometry of root canals differs in different parts, especially in the apical region, and it is affected by different preparation techniques. The aim of this study was to evaluate the geometric changes of root canal preparation by general dentists regardless of the endodontic instrumentation systems and to study the quality of endodontic treatment by evaluating the untouched areas after mechanical preparation and the smear layer removal. Materials and Methods. 100 extracted maxillary canines w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…It's important to note that the selected molar tooth, intended for simulations with various files and operational techniques in the future studies, had not previously undergone root canal treatment. Therefore, its root canal was artificially enlarged based on the data from the literature, taking into consideration the dentin removal resulting from endodontic procedures [18,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It's important to note that the selected molar tooth, intended for simulations with various files and operational techniques in the future studies, had not previously undergone root canal treatment. Therefore, its root canal was artificially enlarged based on the data from the literature, taking into consideration the dentin removal resulting from endodontic procedures [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…[18] and Razumova et al. [19]. The final geometry of the reconstructed root canal was used in the simulation (Figure 7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review published by Yaylali et al showed that PUI was superior over SNI and EA for removing calcium hydroxide from the root canal apical third area [48]. It is more difficult for the irrigation techniques to fully contact with the canal wall because the apical thirds have more lateral canals, apical ramifications, and isthmus than the coronal and middle thirds [99]. In addition to the complex anatomical factors, the phenomenon of vapor lock also prevented the irrigant solutions to penetrate into apical thirds [100].…”
Section: Agreements and Disagreements With Other Studies Or Reviewsmentioning
confidence: 99%
“…A systematic review published by Yaylali et al showed that PUI was superior over SNI and EA for removing calcium hydroxide from the root canal apical third area [101]. It is more di cult for the irrigation techniques to fully contact with the canal wall because the apical third regions have more lateral canals, apical rami cations, and isthmus than the coronal and middle third regions [102]. In addition to the complex anatomical factors, the phenomenon of vapor lock also prevented the irrigant solutions to penetrate into apical third regions [103].…”
Section: Agreements and Disagreements With Other Studies Or Reviewsmentioning
confidence: 99%